Factory worker jobs and the relationship with cardiovascular risk factor in Indonesia - Suyoto, Perdana Samekto Tyasnugroho (Progress in Nutrition, 2018)
Situation at the workplace, including environment and job type influence health status of workers. This study was conducted to learn the relationship between job types in factory setting with cardiovascular risk in Indonesia. A cross-sectional study was conducted on 111 factory workers in an electronic factory in Yogyakarta, Indonesia. Jobs were classified into three category: officers, operators, and technician. Officers are white-collar employees which have low occupational physical activity, while operators and technician are blue collar employees who have higher physical burden. All the subject were measured the body mass index, waist circumference, percent body fat, and total cholesterol. The mean of percent body fat in officers is lower than operators and technicians. No other relationship was found in BMI, waist circumference, and total cholesterol. In conclusion, we found in our study an association between job type and percentage body fat as a cardiovascular risk factor. White collar employees have lower percent body fat than their blue collar counterparts.